The photoprocess effects of an amino group located at different positions along the polymethine chain in indodicarbocyanine dyes. Issue 49 (14th June 2017) - Cao, Jianfang; Fan, Jiangli; Sun, Wen; Guo, Yu; Wu, Hongmei; Peng, Xiaojun
Abstract : The amino group is a-ICT in the even position but is the ICT in the odd position. Abstract : A systematic spectral analysis is presented for Cy3, Cy5, Cy7 and Cy9 aminocyanine dyes. The amino group in different positions of the polymethinic chain causes different background spectral properties. Computational studies on these dyes reveal that the length of C–N bond of amino group in the even position is close to that of the CN double bond, which prevents the conjugation of the whole polymethine chain. The amino group located in the even position acts as the electron acceptor at excited state (a-ICT) of aminocyanine dyes. While, the amino group in the odd position is the electron donor at excited state (ICT) of aminocyanine dyes. The rotations of amino groups are more difficult for aminocyanine dyes with the amino group in the even position than that of the amino group in the odd postion. The results demonstrate a foundation for interpretation of the behavior of the dyes, thus providing guidelines for future design of new aminocyanine fluorophores.